Gestão democrática: uma análise a partir de elementos da obra pedagógica de Paulo Freire - Fagundes, Antonio Ribeiro (2009)
The Democratic Administration is a struggle and conquest process, which has its main links for its execution in dialogue and in political conscience. It falls to the educator to be a promoter of critical sense. It is also necessary to understand that the Democratic Administration is not just pedagogic making. Such proposal should be understood in a wider way, which means, in the perspective of human being participation before an entire systemic reality, considering that transformation, participation and education constitute an inseparable trilogy.